When Risks Collide: Compound Vulnerability to Natural Disasters, Market Fluctuations, and Pandemics – Insight from Enrekang, Indonesia - Astaman, Putra; Hikmah, Aulia Nurul; Dassir, Muhammad; Siregar, Ahmad Ramadhan; Qinayah, Mirnatul; Aisyah, Megawati; Herlyani S. (Tarjih : Agribusiness Development Journal, 2025)
The vulnerability of agrarian communities to shocks, seasonality, and long-term trends is a complex challenge that requires holistic analysis. This study aims to analyze the dynamic interaction between the three dimensions of vulnerability (shock-seasonality-trend) in agrarian communities in disaster-prone areas, using a holistic approach that fills the gap in previous literature, which tends to be partial. Using a qualitative case study approach, data were collected through in-depth interviews (25 key informants), focus group discussions (4 sessions), and secondary document analysis. The findings reveal that: (1) Shocks such as natural disasters and disease outbreaks weaken economic resilience due to infrastructure damage and health costs; (2) Seasonal pressures (pest attacks, price fluctuations) increase income instability, exacerbated by dependence on monoculture and limited market access; (3) Long-term trends (droughts, climate change) threaten agricultural sustainability through extreme weather and declining land productivity. Community adaptation strategies include crop diversification, the formation of savings and loan groups, and the adoption of sustainable agricultural practices, but these are hampered by a lack of institutional and technological support. This study highlights the need for integrated policies that combine ecosystem-based mitigation, strengthening early warning systems, and climate resilience training programs. The study's implications contribute to the literature on multidimensional vulnerability and provide practical recommendations for achieving sustainable community resilience.